PENERAPAN SISTEM MANAJEMEN KUALITAS DALAM MENINGKATKAN KEPERCAYAAN KONSUMEN TERHADAP PRODUK LOKAL UMKM DI KOTA MUARA TEWEH - muhamad Rifai; Muhammad Ikhwan (JURNAL ILMU EKONOMI (MANAJEMEN PERUSAHAAN) DAN BISNIS, 2026)
The purpose of this study is to analyze the implementation of quality management systems and their role in increasing consumer trust in local MSME products in Muara Teweh City. This study also aims to identify aspects of quality management that influence the development of consumer trust, as well as the obstacles faced by MSMEs in implementing them. This study uses a qualitative approach with a descriptive method. The research subjects consisted of local MSME business actors and consumers in Muara Teweh City selected through purposive sampling techniques. Data were collected through interviews, observations, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of quality management systems in MSMEs in Muara Teweh City is still simple and not yet fully standardized, especially in the aspects of SOPs, documentation, and quality control. Nevertheless, the application of quality management principles such as maintaining product consistency, process control, and complaint handling can increase consumer trust. Consumer trust is built through consistent product quality, product safety, and the responsibility of MSME business actors in meeting consumer expectations.